Orthogonal complementary codes for wideband wireless CDMA communications - Lu, Liru. (2008)
The thesis focuses on the study of Orthogonal Complementary Codes for future CDMA wideband wireless communication systems. The upcoming fourth generation wireless communications call for the new technologies which are able to support much higher data rate and multi-media services. The research is conducted in this context seeking an improved and feasible solution of spreading codes for future generation CDMA systems.